2023
DOI: 10.3390/bios13020287
|View full text |Cite
|
Sign up to set email alerts
|

Difunctional Hydrogel Optical Fiber Fluorescence Sensor for Continuous and Simultaneous Monitoring of Glucose and pH

Abstract: It is significant for people with diabetes to know their body’s real-time glucose level, which can guide the diagnosis and treatment. Therefore, it is necessary to research continuous glucose monitoring (CGM) as it gives us real-time information about our health condition and its dynamic changes. Here, we report a novel hydrogel optical fiber fluorescence sensor segmentally functionalized with fluorescein derivative and CdTe QDs/3-APBA, which can continuously monitor pH and glucose simultaneously. In the gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…By ratiometric detection of the intensities of fluorescence of the two NC types, quantitative and selective detection of Fe 3+ ions was achieved in a linear range of 0-3.5 µM, with a detection limit of 14 nM. A similar approach was used by Li et al [100] for engineering a difunctional hydrogel optical fiber fluorescence sensor for continuous and simultaneous monitoring of the glucose level and pH.…”
Section: Biosensors Based On Fluorescent Gelsmentioning
confidence: 97%
“…By ratiometric detection of the intensities of fluorescence of the two NC types, quantitative and selective detection of Fe 3+ ions was achieved in a linear range of 0-3.5 µM, with a detection limit of 14 nM. A similar approach was used by Li et al [100] for engineering a difunctional hydrogel optical fiber fluorescence sensor for continuous and simultaneous monitoring of the glucose level and pH.…”
Section: Biosensors Based On Fluorescent Gelsmentioning
confidence: 97%
“…Optical fibers have been explored substantially for fluorescence spectrometry as well as for obtaining high resolution fluorescence imaging useful for in vivo disease diagnosis applications [2][3][4] . Fluorescent reagents coated on the tip or on the surface of the optical fiber can be used for detection of desired analyte in the sample based on change in the fluorescence properties, mostly fluctuations in fluorescence intensity where the emitted light coupled into the same or different fiber reaches the detector [5][6][7][8][9][10] . However, the measurement of fluorescence intensity suffers from certain limitations such as requirement for filtering of weak fluorescence signal from the source of excitation as well as low sensitivity to molecular change.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al recently reported a fluorescence glucose sensor based on a functionalized hydrogel OF. [ 31 ] The hydrogel was functionalized with fluorescein derivative CdTe QDs/3‐APBA. The hydrogel matrix swells because of the interaction between PBA and glucose molecules, which decreases the fluorescence of quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…The sensors also showed an equilibrium time of 25 min. [31] Similarly, Ahmed et al reported a PBA-based hydrogel sensor with nanostructure imprinted on the OF tip. [36] Aztec nanostructures were introduced to enhance the sensitivity and detection limit of the sensors.…”
mentioning
confidence: 96%
See 1 more Smart Citation